Video Game Art Reader Volume 2 - Funk, Tiffany (Amherst College Press, 2018)
This volume of VGAR critically analyzes video game art as a means of survival. Though "survival strategy" exists as a defined gaming genre, all video games-as unique, participatory artworks-model both individual and collaborative means of survival through play. Video games offer opportunities to navigate both historical and fictional conflicts, traverse landscapes devastated by climate change or nuclear holocaust, and manage the limited resources of individuals or even whole civilizations on earth and beyond. They offer players a dizzying array of dystopian scenarios in which to build and invent, cooperate with others (through other players, NPCs, or AI) to survive another day. Contributors show how video games focus attention, hone visuospatial skills, and shape cognitive control and physical reflexes and thus have the power to participate in the larger context of radical, activist artworks that challenge destructive hegemonic structures as methods of human conditioning, coping, and creating.